2022
DOI: 10.3390/ijms23031268
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetyl-Aspartyl-Glutamate in Brain Health and Disease

Abstract: N-acetyl-aspartyl-glutamate (NAAG) is the most abundant dipeptide in the brain, where it acts as a neuromodulator of glutamatergic synapses by activating presynaptic metabotropic glutamate receptor 3 (mGluR3). Recent data suggest that NAAG is selectively localized to postsynaptic dendrites in glutamatergic synapses and that it works as a retrograde neurotransmitter. NAAG is released in response to glutamate and provides the postsynaptic neuron with a feedback mechanisms to inhibit excessive glutamate signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 137 publications
(164 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, NAALAD2 has molecular specificity for TD because it works on two important, TD-linked neurotransmitters: NAAG and glutamate. NAAG is one of the only CSF markers for which we found genetic sharing with TD and it is thought to function as a neurotransmitter in both the CNS and peripheral nervous system, with its lowest expression being in the pituitary [ 234 ], a finding that is in line with NAALAD2 expression being the highest in this brain region (see above). In a magnetic resonance spectroscopy (MRS) study, patients with TD also had reduced levels of NAA in the left putamen and bilateral frontal cortex [ 191 ].…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, NAALAD2 has molecular specificity for TD because it works on two important, TD-linked neurotransmitters: NAAG and glutamate. NAAG is one of the only CSF markers for which we found genetic sharing with TD and it is thought to function as a neurotransmitter in both the CNS and peripheral nervous system, with its lowest expression being in the pituitary [ 234 ], a finding that is in line with NAALAD2 expression being the highest in this brain region (see above). In a magnetic resonance spectroscopy (MRS) study, patients with TD also had reduced levels of NAA in the left putamen and bilateral frontal cortex [ 191 ].…”
Section: Discussionsupporting
confidence: 63%
“…This process can be reduced with an effective P/Q-type VGCCs modulator (Schurr, 2004;Nimmrich and Gross, 2012). Based on some previous studies on excitotoxicity models, hyperstimulation of glutamate receptors is a result of the administration of NMDA in the rat hippocampus (Jarrard, 2002;Gilmour et al, 2012;Farzamfard et al, 2022;Morland and Nordengen, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Post-synaptic neuronal GRM3 activation by NAAG results in inhibition of downstream signaling, resulting in reduced release of glutamate by post-synaptic neurons and thus may modify neuronal activity in conjunction with co-released glutamate. In epilepsy models, inhibition of the NAAG degradation enzyme (glutamate carboxypeptidase II) and GRM3 agonists module seizure frequency [ 56 ], and activation of GRM3 in traumatic brain injury models indicates a protective effect. With expression in astrocytes, it has been suggested that NAAG may also play a role in mediating inflammatory response.…”
Section: Discussionmentioning
confidence: 99%